Traditional Autumn Pear Varieties in Republic of Macedonia. Proceedings - Miskoska – Milevska, E.; Selamovska, A.; Dimiskovska, B. (Ecological Movement of Novi Sad, 2016)
Five traditional autumn pear varieties (‘Erebasma’, ‘Patligjanka’, ‘Ljubichica’, ‘Shaldanka’ and ‘Tatlikuti’) exist in the Republic of Macedonia. The object of this research was the examination of the phenological, fruit and chemical characteristics of these pear varieties. The pears ‘Erebasma’, ‘Shaldanka’ and ‘Tatlikuti’ formed the biggest fruits. The examined pear varieties contained small number of seeds, approximately 1.4. The pears ‘Ljubichica’, ‘Tatlikuti’ and ‘Shaldanka’ had firm fruits (1428.3-1475.5 g/cm2). The average values of soluble dry matter, total sugar and total acids in these pear varieties were 15.0%, 14.0% and 0.7%, respectively. The fruits of the pears ‘Erebasma’ and ‘Tatlikuti’ had the best flavor.
Keywords: pear, traditional, autumn varieties